2016
DOI: 10.1039/c6ra02566h
|View full text |Cite
|
Sign up to set email alerts
|

Isocoumarins and benzofurans from the mangrove endophytic fungus Talaromyces amestolkiae possess α-glucosidase inhibitory and antibacterial activities

Abstract: Six new isocoumarins, compounds1–4and14–15, two new benzofurans,16–17, along with nine known isocoumarin analogues,5–13were obtained from the mangrove endophytic fungusTalaromyces amestolkiaeYX1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 34 publications
0
71
0
Order By: Relevance
“…It was obtained using the standard protocol for the isolation of endophytic microbes [8]. This isolate was identified by Yayue Liu and assigned the accession number ZJ-SY 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was obtained using the standard protocol for the isolation of endophytic microbes [8]. This isolate was identified by Yayue Liu and assigned the accession number ZJ-SY 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In the past decades, our research group had been focusing on the exploration of new bioactive metabolites from mangrove endophytic fungi collected from the South China Sea [6,7,8,9,10,11,12,13]. The EtOAc extract of the fermentation of a mangrove endophytic fungus, Penicillium sp.…”
Section: Introductionmentioning
confidence: 99%
“…The assays for antibacterial [23] and α-glucosidase inhibitory [23] were carried out as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…50 µg/mL)[61]. Chen et al reported that the isocoumarins metabolites were separated from Talaromyces amestolkiae, did not exhibit any antibacterial activity against Staphylococcus epidermidis, S. aureus, Klebsiella pneumoniae, E. coli, and B. subtilis[62]. were biosynthesized by Aspergillus banksianus, were tested for in vitro antimicrobial activities against E. coli (ATCC 25922), B. subtilis (ATCC 6633), Saccharomyces cerevisiae (ATCC 9763), and C. albicans (ATCC 10231).…”
mentioning
confidence: 99%